Static Versus Dynamic Stimuli in Story Retelling: First Mentions of Main Characters in Sign Language Narratives. - Gür, Cansu; Sümer, Beyza (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Task design plays a central role in linguistic elicitation, yet its impact on sign language production, especially with respect to stimulus type, remains underexamined. This study investigates how two commonly used narrative visual stimuli, a static picture sequence and a dynamic video clip, affect referent introduction at the first mention of main characters in Turkish Sign Language (TİD). Method: Twenty early signers of TİD (10 children, 10 adults) participated in a within-subject narrative retelling task. Their use of lexical signs (LSs), classifier predicates (CLs), and other linguistic strategies was annotated and analyzed using a Bayesian multilevel multinomial logistic regression. Results: Across both age groups, LS emerged as the dominant referential strategy, with minor variations in the use of CL and other strategies between static and dynamic conditions. No statistically significant differences were found by age or stimulus type. Conclusions: These findings highlight the relative robustness of referent introduction in signed narratives, regardless of stimulus type. The study offers methodological insight into stimulus selection in sign language research and contributes to ongoing debates about task comparability, ecological validity, and modality-specific discourse strategies.